Recuerdos en el espejo: memoria, ideología y agencialidad en Los cuentos de final y Alfonso y Clotilde de Carlos Manuel Varela - Kark, Christopher (Latin American Theatre Review, 2010)
The restrictions imposed on the Uruguayan theatre community during the militarydictatorship between 1973 and 1985 prohibited direct references to the country’s politicalsituation. As a result, playwrights of the era developed a technique that Carlos Manuel Varelaterms “hallucinatory realism,” which masks subversive content through ambiguous wording,allegory and appeals to memory meant to be understood by the audience and escape censorship.Using recent theoretical writings on ideology, cultural memory and Judith Butler’s notion of“agency,” this paper asserts that two plays by Varela — Los cuentos del final and Alfonso yClotilde — embody this technique both as texts and as a means of preserving public discourse,thereby exceeding the regime’s limits of power. (CK, Article in Spanish)